The Oxford handbook of project management - Morris, Peter W. G.; Pinto, Jeffrey K.; Söderlund, Jonas (Oxford : Oxford University Press, 2011)
This handbook presents and discusses leading ideas in the management of projects, drawing on the insights of over 40 scholars to chart the development of the subject over the last 50 years as an area of increasing practical and academic interest.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Project management